2022
DOI: 10.1093/schizbullopen/sgac022
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of a Multidisciplinary Lifestyle-Enhancing Treatment for Inpatients With Severe Mental Illness: The MULTI Study V

Abstract: Economic evaluations of lifestyle interventions for people with mental illness are needed to inform policymakers and managers about implementing such interventions and corresponding reforms in routine mental healthcare. We aimed to evaluate changes in healthcare costs 18 months after the implementation of a multidisciplinary lifestyle-enhancing treatment for inpatients with severe mental illness (MULTI) versus treatment as usual (TAU). In a cohort study (n=114; 65 MULTI, 49 TAU), we retrospectively retrieved c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Although physical activity should be encouraged for all people with schizophrenia or bipolar disorder, owing to resource constraints of healthcare systems the provision of a multicomponent lifestyle intervention including a PAI component might need to be limited to those people who are mostly likely to benefit from it. Based on the limited evidence, it is suggested that the following patient subgroups might be more likely to benefit from a multicomponent lifestyle intervention including a PAI component: men; 43 individuals with comorbid type 2 diabetes; 12 and individuals who have been psychiatric hospital in-patients for ≥1 year 42 . Further research is urgently needed to confirm the differential impacts of using multicomponent lifestyle interventions including a PAI component on different patient subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although physical activity should be encouraged for all people with schizophrenia or bipolar disorder, owing to resource constraints of healthcare systems the provision of a multicomponent lifestyle intervention including a PAI component might need to be limited to those people who are mostly likely to benefit from it. Based on the limited evidence, it is suggested that the following patient subgroups might be more likely to benefit from a multicomponent lifestyle intervention including a PAI component: men; 43 individuals with comorbid type 2 diabetes; 12 and individuals who have been psychiatric hospital in-patients for ≥1 year 42 . Further research is urgently needed to confirm the differential impacts of using multicomponent lifestyle interventions including a PAI component on different patient subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarises the characteristics of the nine included studies. All included studies were conducted in high-income countries: the UK (4/9, 44.4%), 12,13,37,38 the USA (2/9, 22.2%), 39,40 The Netherlands (2/9, 22.2%) 41,42 and Belgium (1/9, 11.1%). 43 The settings of the interventions were community mental health services (5/9, 55.6%), [37][38][39][40][41] primary care (2/9, 22.2%), 12,13 a sheltered housing organisation (1/9, 11.1%) 43 and in-patient care (1/9, 11.1%).…”
Section: Study Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…To support decision-making in implementing lifestyle interventions, costeffectiveness evaluations are essential and, although a few studies have reported on these in mental health care, evidence is still scarce (40)(41)(42)(43)(44)(45). We therefore also conducted an economic evaluation alongside the trial investigating the costeffectiveness and cost-utility of the SMILE intervention with respect to usual care.…”
Section: Translation Of Research Into Daily Practicementioning
confidence: 99%
“…An increasing number of clinical guidelines for mental health care for people with SMI include a focus on physical health (4). Although many studies have been conducted (4,27), evidence for long-term sustainability of lifestyle interventions for people with SMI is still limited (40,57,151,152), and implementation into routine care is lacking (40,68). Also, little is known regarding the cost-effectiveness of lifestyle interventions within this population as studies often do not describe cost data or address cost-effectiveness (4,38,57,153).…”
Section: Introductionmentioning
confidence: 99%